Budaya Organisasi, Pengembangan Karir, Job Insecurity Terhadap Organisational Citizenship Behaviour Dengan Komitmen Organisasional Sebagai Variabel Intervening - Ni Luh Putu Krishna Udayani; Ni Nyoman Sunariani (Universitas Pendidikan Nasional, 2018)
ABSTRACTResearch conducted at Hotel The Samaya Ubud Bali aims to determine the influence of organizational culture on organizational commitment. To determine the effect of career development on organizational commitment. To know the influence of job insecurity on organizational commitment. To know the effect of organizational commitment to OCB. To know the effect of organization culture to OCB. To identify the influence of career development on OCB. To know the influence of job insecurity on OCB. Data collection using questionnaire. Sampling technique using non probability sampling with sample saturated as many as 130 respondents. Data analysis technique used in this research is by using SEM (Structural Equation Modeling) with program of AMOS for Windows version 22. The result of research shows the influence of latent variable organizational culture (X1) to the latent variable organizational commitment (Y1) is positively significant. The influence of latent variable career development (X2) on the latent variable organizational commitment (Y1) is positively significant. The influence of latent variable Job Insecurity (X3) to the latent variable organizational commitment (Y1) is negatively significant. The influence of the latent variable organizational commitment (Y1) to the latent variable OCB (Y2) is positively significant. The influence of latent variable culture organization (X1) to latent variable OCB (Y2) is positively significant. The influence of latent variable career development (X2) on OCB latent variable (Y2) is positively significant. The influence of latent variable job insecurity (X3) to the latent variable OCB (Y2) is negatively significant.